2023
DOI: 10.1177/1420326x231152561
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the objective and subjective physical environments of residential care facilities

Abstract: The aim of this research was to explore the objective and subjective physical environments of residential care facilities (RCFs) by studying 34 facilities in Harbin, Changchun, Shenyang and Dalian. A study that combines questionnaires and instrumental testing. Pearson’s correlation and regression analysis were used to analyse the correlation between the measured value and the evaluation result and the impact on the results of the participants’ personal background evaluations. The results showed that the bright… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…62 The impact of the lighting on care home residents' living conditions is significant. 63 Older people with dementia staying in low illuminance environments could show more signs of a negative mood, thus impacting their well-being. 64 A comfortable indoor light environment compensates for the deteriorating eyesight of older people and benefits the quality of life, such as regulating circadian rhythm and decreasing depression.…”
Section: Discussionmentioning
confidence: 99%
“…62 The impact of the lighting on care home residents' living conditions is significant. 63 Older people with dementia staying in low illuminance environments could show more signs of a negative mood, thus impacting their well-being. 64 A comfortable indoor light environment compensates for the deteriorating eyesight of older people and benefits the quality of life, such as regulating circadian rhythm and decreasing depression.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study in older residents (householders 75−79 years of age) revealed that objective (structural adequacy, maintenance quality) and subjective (overall satisfaction with housing rated by subjects) data were significantly related, but the objective data only explained 4.8−18.5% of the subjective ratings (Christensen et al, 1992). In a recent study investigating the correlations between objectively measured versus subjective ratings of environmental variables in the home across 34 care facilities in China, it was found that the magnitude of correlations varied across examined parameters (e.g., humidity, lighting, acoustic properties, and air quality), but they were all positive and most of them were significant (Mu et al, 2023). Generally, a complementary approach that integrates subjective and objective data might be an optimal solution to explain overall satisfaction with the home environment (Chen et al, 2022), and relatedly mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%